Epidemiology, risk factors and outcomes of prolonged mechanical ventilation with different cut-points in a PICU - Chongcharoenyanon, Tatchanapong; Samransamruajkit, Rujipat; Sophonphan, Jiratchaya (Frontiers in Pediatrics, 2023)
Background: A consensus on the definition of prolonged mechanical ventilation (PMV) for children does not exist. There is still lack of published work presenting the epidemiology, risk factors and outcomes at different cut-points for PMV patients. These are important for planning the goals of treatment and counseling of the prognosis for patient families. We aimed to determine the incidence, baseline characteristics, risk factors and outcomes of PMV in pediatric patients at various cut-points (>14, >21 or >30days). Methods: A retrospective cohort study among children <18-years-old who were PMV>14 days in the PICU of King Chulalongkorn Memorial Hospital was conducted. The primary outcomes were incidence of PMV with various cut-points. We stratified patients into three groups (Group1; PMV >14-21, Group2; >21-30, Group3; >30 days) for evaluating the baseline characteristics, risk factors, and outcomes of PMV (extubation success, tracheostomy status and death). Factors associated with PMV and non-survivors were analyzed using univariate and multivariate logistic regression. Results: From January 2018 to August 2022, 1,050 patients were screened. Of these, 114 patients were enrolled. The incidence of PMV >14, >21 and >30 days were 10.9%, 7.3% and 5.0% respectively. Extubation success was significantly lower in Group3 than in Groups1 & 2 (15.4% versus 62.2% & 56.0%, P<0.001). Consequently, the tracheostomy rate (63.5% versus 16.2% & 12.0%, P<0.001), VAP rate (98.1% versus 59.5% & 80.0%, P<0.001), mortality rate by disease (34.6% versus 5.4% & 20.0%, P=0.003), median PICU LOS (50.5 versus 22.0 & 28.0 days, P<0.001) and median hospital LOS (124.5 versus 55.0 & 62.0 days, P<0.001) were also significantly higher for Group3 compared with Groups 1 & 2. The factor associated with PMV >30 days was VAP (aOR19.53, 95%CI 2.38-160.34, P = 0.01). Factors associated with non-surviving patients were 3rd degree PEM (aOR5.14, 95%CI 1.57-16.88, P=0.01), PIM3 score ≥14 (aOR6.75, 95%CI 2.26-20.15, P<0.001) and muscle relaxant usage (aOR5.58, 95%CI 1.65-18.86, P=0.01). Conclusion: Extubation failure, tracheostomy rate, VAP rate, mortality rate by disease, PICU LOS and hospital LOS were significantly higher for PMV >30 days. Consequently, we suggest that a 30 day duration as a cut-point for PMV in PICUs might be more appropriate.